Nutritional quality of fritters produced from fresh cassava roots, high-quality cassava and soy flour blends, and consumer preferences - Alamu, Emmanuel Oladeji; Ntawuruhunga, P.; Chileshe, P.; Olaniyan, B.; Mukuka, I.; Maziya-Dixon, Busie (Informa UK Limited, 2019)
Fritters are flour-based snacks made from wheat flour, but a cheaper alternative is needed in a developing economy, such as Zambia, owing to the high cost of wheat. This study aimed at evaluating fritters produced from different sources: fresh cassava roots, high-quality cassava flour (HQCF), and a composite (80:20) of HQCF and high-quality soy flour (HQSF) using 100% wheat flour as the control. The nutritional and anti-nutritional properties were analyzed with standard laboratory methods. A structured questionnaire was used to analyze consumer preferences. There were significant (P < 0.05) differences in the proximate parameters of the fritters samples. In HQCF fritters, amylose increased by 12.26%, sugar by 11.12%, and starch by 27.91%. There were no significant (P > 0.05) differences in the antinutritional properties among cassava and wheat fritters except for the composite cassava‒soybean fritters. Among respondents from Kaoma, Kasama, and Serenje, the sensory characteristics showed no significant (P > 0.05) differences for appearance and aroma of all the fritters samples. The results showed that HQCF fortified with HQSF could be used as a cheaper alternative to wheat flour in the production of nutritious and acceptable fritters.